2019
DOI: 10.1002/essoar.10501113.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The enigma of Neoproterozoic giant ooids-Fingerprints of extreme climate?

Abstract:  Giant ooids are a rare carbonate facies that occur in strata underlying a number of Neoproterozoic glacial deposits.  Giant ooid diameter was applied to constrain Neoproterozoic seawater carbonate saturation state, temperature, and alkalinity.  Neoproterozoic giant ooids indicate hot or cold, but not moderate, climate at low latitudes preceding the onset of glaciations.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…For example Trower et al. (2017), developed an Ω proxy for carbonate minerals based on the size of coated grains such as ooids, which has subsequently been applied to questions about Neoproterozoic climate (Trower, 2020). Other approaches have been developed based on carbonate textures and accessory minerals in large evaporite basins (Pope et al., 2000); however, a drawback of this approach is that large evaporite basins are unevenly distributed in the rock record (Babel & Schreiber, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For example Trower et al. (2017), developed an Ω proxy for carbonate minerals based on the size of coated grains such as ooids, which has subsequently been applied to questions about Neoproterozoic climate (Trower, 2020). Other approaches have been developed based on carbonate textures and accessory minerals in large evaporite basins (Pope et al., 2000); however, a drawback of this approach is that large evaporite basins are unevenly distributed in the rock record (Babel & Schreiber, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Cathodoluminescence (CL) characteristics of a subset of thin sections were analyzed using a Technosyn (Cambridge Image Technology Limited, Cambridge, UK) cold cathodoluminescence unit with beam settings of ca 14 KV and a gun current of ca 400 mA. Exposure times for CL images varied with most exposures lasting 1 to 5 s. Trower et al (2017Trower et al ( , 2018Trower et al ( , 2020 demonstrated that ooid size reflects an equilibrium between precipitation and abrasion rates, which supports the application of ooid size measurements in the rock record to reconstruct Ω of ancient seawater or lake water (Li et al, 2020;Trower, 2020). Ooid diameters were measured from thin sections using JMicrovision (Roduit, 2020); when possible, 400 grains were measured per sample, but some samples contained <400 usable grains.…”
Section: Field Geology Sedimentology and Petrographymentioning
confidence: 84%
“…Trower et al . (2017, 2018, 2020) demonstrated that ooid size reflects an equilibrium between precipitation and abrasion rates, which supports the application of ooid size measurements in the rock record to reconstruct Ω of ancient seawater or lake water (Li et al ., 2020; Trower, 2020). Ooid diameters were measured from thin sections using JMicrovision (Roduit, 2020); when possible, 400 grains were measured per sample, but some samples contained <400 usable grains.…”
Section: Methodsmentioning
confidence: 99%
“…The combination of abundant marine cementation, early lithification of oolitic sediment, the growth of giant ooids at the platform margins, and ample carbonate production rates to produce exceedingly thick, high‐relief platforms, points to elevated sea water calcium carbonate saturation during the Early Triassic. The modelling of ooids in Neoproterozoic platforms (Sumner & Grotzinger, 1993; Trower, 2020) and the Early Triassic GBG (Li et al, 2020b) suggest that the genesis of giant ooids requires elevated sea water carbonate saturation. A factor common to both Neoproterozoic and Early Triassic systems is the absence of or greatly reduced skeletal calcium carbonate precipitation that would have resulted in high sea water carbonate saturation and a shift to precipitation of abiotic and microbial components (cf.…”
Section: Interpretation and Discussionmentioning
confidence: 99%